2003
DOI: 10.1076/phbi.41.6.412.17828
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and Anti-inflammatory Activity of the Genus Echinacea

Abstract: The antifungal activity and 5-lipoxygenase-inhibiting activity of extracts of five wild and three commercially used taxa of the genus Echinacea were investigated. The near-UV mediated antifungal bioassays included clinically isolated Cryptococcus neoformans, two Candida albicans isolates (D10 and CN1A) with amphotericin B resistance, as well as established and emerging filamentous fungal pathogens (Trichophyton tonsurans, T. mentagrophytes, Microsporum gypseum and Pseudallescheria boydii). Root extracts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…Inflammatory responses mediated through induced arachadonic acid metabolism can occur by the lipoxygenase (LOX) pathway, which is responsible for leukotriene (LT) synthesis, or the cyclooxygenase (COX) pathway, which results in the production of various prostaglandins (PG) [30]. Aloe protein exhibited both LOX and COX inhibitory activity which suggests this protein may be clinically useful to reduce LT and PG synthesis in the inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory responses mediated through induced arachadonic acid metabolism can occur by the lipoxygenase (LOX) pathway, which is responsible for leukotriene (LT) synthesis, or the cyclooxygenase (COX) pathway, which results in the production of various prostaglandins (PG) [30]. Aloe protein exhibited both LOX and COX inhibitory activity which suggests this protein may be clinically useful to reduce LT and PG synthesis in the inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…UV light-mediated antifungal activity was reported for extracts of some Echinacea species. In this case the combination of high levels of the C 12 tetraene amides 65a/66a together with various polyacetylenes exhibited a very effective phototoxic action against a variety of clinically isolated humanpathogenic fungi (Merali et al 2003). In a more recent study the hypothesis was tested, that alkamides from Echinacea exert antifungal activity by disrupting the fungal cell wall/membrane complex (Cruz et al 2014).…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 97%
“…Anti-candida activity for E. purpurea extracts has also been described previously (Barrett 2003). In contrast, n-hexane extracts of the fresh roots of E. pallida var pallida and E. pallida var angustifolia (identified according to a revised taxonomy after Binns et al 2002a) showed no measurable inhibition of C. albicans, but an amphotericin-B-resistant strain (D10) of C. albicans and Tricophyton mentagrophytes were susceptible to E. pallida var pallida root extract in the presence of UV light (Merali et al 2003).…”
Section: Antifungal and Antibacterial Activitiesmentioning
confidence: 99%
“…Inhibition of 5-lipoxygenase has also been described for extracts of roots of E. purpurea, E. pallida var pallida and E. pallida var angustifolia (identified according to a revised taxonomy after Binns et al 2002a). IC50 (inhibitory concentration) values (g root mL À1 assay volume) were 0.642, 1.08 and 0.444, respectively, and corresponding alkamide concentrations in the root of each species were 0.05%, trace and 0.2%, respectively (Merali et al 2003).…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%